Impact of Environmental Geographic toward Point Mutations in Exon 1 of Growth Differentiation Factor (GDF9) Gene in Kosta and Lakor Goat Breeds - Maman Rumanta; Rony Marsyal Kunda; Slamet Diah Volkandari; Ivan Mambaul Munir (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the impact of environmental biogeography on point mutations in Kosta and Lakor goat breeds as local Indonesian germplasm using the GDF9 Exon 1 gene sequence. A total 43 folicle samples of Kosta and Lakor goats which collected in Serang regency and Lakor island were analyzed. To isolate the total genome of the samples, the tissue isolation method was used. The polymerase chain reaction (PCR) method was used for amplification of the exon-1 region of the GDF9 gene with two pairs of primers. Analysis of genetic variation and single nucleotide polymorphisms (SNP) using MEGA software version X. Multiple alignment results showed that there are 2 nucleotides that have mutations, but not encode different amino acids. This results indicates that the mutation has association with litter size of two breeds. This finding shows that Lakor goats have polymorphism i.e SNP g.54C>T which is significantly associated with litter size. The analysis of GDF9 gene showed that all samples from the Two local Indonesian goat breeds (Kosta and Lakor) areÂ  monomorphic. But, although both are monomorphic, geographical isolation still contributes to genetic drift within and between populations.